Manajemen Sumber Daya Insani Dalam Pengelolaan Heritage Pesantren Sebagai Potensi Pariwisata Halal Madura: Studi Kasus Pondok Pesantren Annuqayah - Isnaini Nur Afifah, Dony Burhan Noor Hasan (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The purpose of this study describes the management of pesantren heritage by human resources which includes planning, recruitment, and evaluation of human resource development in boarding schools. This research uses a qualitative descriptive approach. The location of this study is in Pondok Pesantren Annuqayah Guluk-Guluk Sumenep. Data collection techniques using interview, documentation and observation methods. Informants in this study are caregivers and caretakers of regional and central boarding schools. The form of data in this study is primary data and secondary data obtained from informants and supporting documents. Analysis of data through descriptive analysis. The results showed that the heritage of Annuqayah pesantren in the form of (1) manuscripts of books written by the caretakers of pesantren huts, Jami'Mosque, and Asta founder of Annuqayah pesantren; (2) Human resource management in the management of heritage pesantren includes analysis of human resource development, recruitment process, education and training programs, formation of pesantren culture, as well as evaluations that are emphasized on behavior changes in carrying out tasks and responsibilities.